Impact of authentic leadership on employee turnover intention: Perceived supervisor support as mediator and organizational identification as moderator - Jun, Kiho; Hu, Zhehua; Sun, Yi (Frontiers in Psychology, 2023)
Authentic leadership is considered a critical factor for retaining talented employees. However, despite fruitful findings, researchers have paid little attention to how authentic leadership is associated with employee turnover intention. Drawing on organizational support theory, justice literature, and social identity theory, we examine the effects of supervisors’ authentic leadership on employee turnover intention to better understand how authentic leaders reduce employees’ turnover intention in Asian context. In this study, we focus on the mediating role of perceived supervisor support (PSS) and the moderating role of organizational identification in the relationship between supervisors’ authentic leadership and employee turnover intention. To test our hypothesized research model, we adopted a cross-sectional design with a convenience data sampling. We also used a self-report research design in the current study. We collected data from 433 employees from several organizations in Korea. Our respondents rated their immediate supervisors’ authentic leadership and their PSS, turnover intention and organizational identification. Confirmatory factor analysis, regression analysis, and moderated mediation analysis revealed that: authentic leadership negatively predicted employee turnover intention In addition, PSS completely mediates the relationship between authentic leadership and employee turnover intention. Furthermore, organizational identification moderates the relationship between PSS and turnover intention. Lastly, organizational identification moderates the mediating effect of PSS on the relationships between perceptions of authentic leadership and employee turnover intention, Herein, we discuss the managerial implications and future research directions arising from our study.